Strategi Kepala Sekolah Dalam Mengelola Konflik Internal Untuk Mencapai Kinerja Sekolah Yang Optimal - Manzil Silsa Sabila; Dwi Dimiati Hartini; Ayu Rita Risky Rani; Siti Zainiyah; Mu’alimin Mu’alimin (JURNAL RISET MANAJEMEN (JURMA), 2024)
In an organization, conflict is an unavoidable aspect that always arises in every collaborative relationship among individuals, groups, and organizations. Although conflict can have positive effects on the development of a school within certain limits, it must be managed carefully to avoid detrimental consequences. The school principal, as the highest leader, has the responsibility to manage conflict effectively, ensuring that it brings positive benefits and avoids negative impacts. This study aims to explore the strategies employed by school principals in managing internal conflicts to achieve optimal school performance. The method used is a literature review with a qualitative approach. The findings indicate that principals apply three strategies in conflict management: collaboration, accommodation, and compromise. These three strategies have proven effective in reducing and preventing the potential for social upheaval within the school environment.